The impact of the implemented lanthanum on the chemical composition of barley crops in conditions of vegetation experiment - I. A. Fastovets; A. D. Kotel’Nikova; O. B. Rogova; N. I. Sushkov; D. S. Volkov; M. A. Proskurnin; Ye. B. Pashkevich (Бюллетень Почвенного института им. В.В. Докучаева, 2017)
In conditions of the vegetation experiment with barley under the artificial illumination, we assessed the ability of lanthanum, which is one of the most widely spread lanthanons, to accumulate in leaves and stems of plants. Also we assessed its ability to affect the elemental composition, biomass and chlorophyll and carotinoides content of plants. The separate studies allowed us to investigate the impact of lanthanum on root length and coleoptiles of barley seedlings. It is shown that La3+ is able to depress significantly the growth of rootlet if its concentration will exceed 10 mg/l and simultaneously stimulate the growth of coleoptile at the concentration exceeding 50 mg/l. The vegetation experiment showed the significant accumulation of lanthanum in the leaves and stems beginning from the exceeding the concentration of 20 and 50 mg/kg of lanthanum within the soil. It is marked that the accumulation of lanthanum in leaves is higher than in stems. The significant decrease of the chlorophyll and carotinoides in the variant with the implementation of 100 mg/kg of lanthanum comparing to the control and the accumulation of ground biomass at the concentration of the implemented lanthanumof 100-200 mg/kg. Theaccumulationofbiomass, whichwasrevealed in the vegetation experiment, correlates with the stimulating impact of lanthanum on the elongation of coleoptile. Taking into account the simultaneous decrease of the root length, the elongation of coleoptile may be explained by the hormonal process. The results obtained may be useful for re-assessment of the security of the implementation of lanthanons in agriculture and the impact of lanthanum on the biochemical processes in plants.